2017
DOI: 10.1371/journal.pone.0183131
|View full text |Cite
|
Sign up to set email alerts
|

Beyond HIV-serodiscordance: Partnership communication dynamics that affect engagement in safer conception care

Abstract: IntroductionWe explored acceptability and feasibility of safer conception methods among HIV-affected couples in Uganda.MethodsWe recruited HIV-positive men and women on antiretroviral therapy (ART) (‘index’) from the Uganda Antiretroviral Rural Treatment Outcomes cohort who reported an HIV-negative or unknown-serostatus partner (‘partner’), HIV-serostatus disclosure to partner, and personal or partner desire for a child within two years. We conducted in-depth interviews with 40 individuals from 20 couples, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 75 publications
(69 reference statements)
0
25
0
1
Order By: Relevance
“…Another barrier to SCS access among HIV affected couples is challenges with HIV serostatus disclosure [22, 24, 45, 49, 50, 64]. Prior studies have shown that serostatus disclosure can be facilitated by couples’ HIV counseling and testing which provides a counselor-mediated venue for serostatus disclosure and is also an opportunity to reach HIV-affected couples to discuss their fertility goals [81, 82] and potentially improve their ability to communicate about safer conception.…”
Section: Discussionmentioning
confidence: 99%
“…Another barrier to SCS access among HIV affected couples is challenges with HIV serostatus disclosure [22, 24, 45, 49, 50, 64]. Prior studies have shown that serostatus disclosure can be facilitated by couples’ HIV counseling and testing which provides a counselor-mediated venue for serostatus disclosure and is also an opportunity to reach HIV-affected couples to discuss their fertility goals [81, 82] and potentially improve their ability to communicate about safer conception.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of male partners in influencing reproductive decision-making has been described. Generally, and regardless of serostatus, male partners have been shown to have great influence on having another child, but receive minimal counselling about the benefits of spacing, options for safer pre and conception practices [ 8 , 25 – 27 ]. Nieves and colleagues also noted that partner’s fertility desire was independently associated with women’s contraceptive use [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Men in Uganda have often been regarded as unsupportive of their partner’s use of family planning [ 28 ] and some studies show that poor communication within partnerships may make it challenging for men to be involved [ 8 ]. In our study, 78% of the women reported that their partners knew they were on family planning, the rest choosing not to disclose it, while 14% of the sexual partners reportedly disapproved their partners using contraception.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unequal gender power dynamics within sex-opposite couples have led men, regardless of who is living with HIV, to play a dominant role in decisions about fertility, determining if, how and when to conceive [9,20]. For example, Matthews et al [19], in their study with PLWH on ART who reported a partner living without HIV or a partner with unknown serostatus, suggested that many couples made incorrect assumptions about their partner's desires, had disparate understandings about HIV transmission and disagreed on the acceptable level of HIV risk to meet reproductive goals. This study also reinforced the importance of assessing and supporting disclosure of HIV status between partners, which is required for effective use of some safer conception options, as timed intercourse [9].…”
mentioning
confidence: 99%